ANALISIS PENGARUH ABU TERBANG (ABU SEKAM PADI) TERHADAP STABILITAS DAN KEPADATAN AC-WCNR - Farlin Rosyad; Juliansyah Juliansyah; Wahyuni Wahab (Rang Teknik Journal, 2024)
Asphalt concrete is a flexible pavement structure mixed with asphalt concrete which is composed of fine aggregate, coarse aggregate and filler material, with asphalt also as a binder. Rice husk ash is the result of burning rice husk waste. Rubber asphalt is a natural polyterpene synthesized through the enzymatic polymerization of isopentyl pyrophosphate. SIR 20 solid natural rubber is made from coagol (used latex) with an impurity content of 0.2 or processed products such as lamps, sitangin. The aim and objective of this research is to determine the effect of fly ash (rice husk ash) on the stability and density of AC-WCNR and to determine the optimum mixture value of AC-WCNR. The research method is a quantitative method that collects data from the results of experimental research in the form of numbers and can be calculated and is in numerical form. The fineness of rice husk ash to AC-WCNR asphalt increases the stability and density of the mixture up to zone 2 with a percentage of rice husk ash of 4%. The standard Marshall stability value increased in zone 2 with a rice husk ash percentage of 4%, amounting to 1294.9 Kg. The density value increased by 2.287 gr/cc in zone 2 with a percentage of 4%. The optimum value for using rice husk ash content is in zone 2 with a percentage of 4%.Keywords: Asphalt Concrete, Rubber Asphalt, Rice Husk Ash, Stability, Density